Mapeamento da cobertura arbóreo-arbustiva em quatro bairros da cidade de Uberlândia-MG - Melazo, Guilherme Coelho (2008)
The disorderly growth of urban areas has drawn man s attention to changes in the environmental quality. Because of the accumulation of environment problems in recent times managing vegetation in urban centers has become a serious challenge. Since people can benefit from vegetation, especially arboreal one, this research aimed to establish quantitative indexes of vegetation and its spatial distribution in the neighborhoods of Center, Jardim Karaíba, Morumbi, and Santa Mônica in the city of Uberlândia, state of Minas Gerais. It was calculated an Index of Vegetation Coverage (IVC) and an Index of Vegetation Coverage per Inhabitant (IVCI), which make possible both to transmit original scientific and technical information synthetically and to understand complex phenomena, by quantifying them so that different segments of society can analyze them. Once applied to the environment, these indexes allow one to compare pressures in systems, assess trends over the time of its state and give the answers suggested by leaders and society. The vegetation coverage mapping was made through the SPRING 4.3 and ARC GIS 9.2 softwares and its techniques of digital image processing. Vegetation coverage s mapping and index calculation aimed to show environmental conditions/symptoms to establish goals from initial data. Results revealed, among other problems, a low rate of vegetation, which is poorly distributed in the urban area. Therefore, geographic information systems are a fundamental instrument for the development of entries which permit to analyze vegetation coverage and for the process of making decisions with regard to planning, projecting, and environmental managing.